The Therapeutic Effect of Human Embryonic Stem Cell-Derived Multipotent Mesenchymal Stem Cells on Chemical-Induced Cystitis in Rats - Lee, Sang Wook; Ryu, Chae-Min; Shin, Jung-Hyun; Choi, Daeheon; Kim, Aram; Yu, Hwan Yeul; Han, Ju-Young; Lee, Hye-Yeon; Lim, Jisun; Kim, Yong Hwan; Heo, Jinbeom; Lee, Seungun; et al. (International neurourology journal, 2018)
To evaluate the therapeutic effect of human embryonic stem cell (hESC)-derived multipotent mesenchymal stem cells (M-MSCs) on ketamine-induced cystitis (KC) in rats. To induce KC, 10-week-old female rats were injected with 25-mg/kg ketamine hydrochloride twice weekly for 12 weeks. In the sham group, phosphate buffered saline (PBS) was injected instead of ketamine. One week after the final injection of ketamine, the indicated doses (0.25, 0.5, and 1×10 cells) of M-MSCs (KC+M-MSC group) or PBS vehicle (KC group) were directly injected into the bladder wall. One week after M-MSC injection, the therapeutic outcomes were evaluated via cystometry, histological analyses, and measurement of gene expression. Next, we compared the efficacy of M-MSCs at a low dose (1×10 cells) to that of an identical dose of adult bone marrow (BM)-derived MSCs. Rats in the KC group exhibited increased voiding frequency and reduced bladder capacity compared to rats of the sham group. However, these parameters recovered after transplantation of M-MSCs at all doses tested. KC bladders exhibited markedly increased mast cell infiltration, apoptosis, and tissue fibrosis. Administration of M-MSCs significantly reversed these characteristic histological alterations. Gene expression analyses indicated that several genes associated with tissue fibrosis were markedly upregulated in KC bladders. However the expression of these genes was significantly suppressed by the administration of M-MSCs. Importantly, M-MSCs ameliorated bladder deterioration in KC rats after injection of a low dose (1×10 ) of cells, at which point BM-derived MSCs did not substantially improve bladder function. This study demonstrates for the first time the therapeutic efficacy of hESC-derived M-MSCs on KC in rats. M-MSCs restored bladder function more effectively than did BM-derived MSCs, protecting against abnormal changes including mast cell infiltration, apoptosis and fibrotic damage.